Intermedin Alleviates Vascular Calcification in CKD through Sirtuin 3-Mediated Inhibition of Mitochondrial Oxidative Stress - Shi-Meng Liu; Ya-Rong Zhang; Yao Chen; Deng-Ren Ji; Jie Zhao; Su Fu; Mo-Zhi Jia; Yan-Rong Yu; Chao-Shu Tang; Wei Huang; Ye-Bo Zhou; Yong-Fen Qi (MDPI AG, 2022)
Vascular calcification (VC) is a common pathophysiological process of chronic kidney disease (CKD). Sirtuin 3 (Sirt3), a major NAD+-dependent protein deacetylase predominantly in mitochondria, is involved in the pathogenesis of VC. We previously reported that intermedin (IMD) could protect against VC. In this study, we investigated whether IMD attenuates VC by Sirt3-mediated inhibition of mitochondrial oxidative stress. A rat VC with CKD model was induced by the 5/6 nephrectomy plus vitamin D3. Vascular smooth muscle cell (VSMC) calcification was induced by CaCl2 and β-glycerophosphate. IMD1-53 treatment attenuated VC in vitro and in vivo, rescued the depressed mitochondrial membrane potential (MMP) level and decreased mitochondrial ROS levels in calcified VSMCs. IMD1-53 treatment recovered the reduced protein level of Sirt3 in calcified rat aortas and VSMCs. Inhibition of VSMC calcification by IMD1-53 disappeared when the cells were Sirt3 absent or pretreated with the Sirt3 inhibitor 3-TYP. Furthermore, 3-TYP pretreatment blocked IMD1-53-mediated restoration of the MMP level and inhibition of mitochondrial oxidative stress in calcified VSMCs. The attenuation of VSMC calcification by IMD1-53 through upregulation of Sirt3 might be achieved through activation of the IMD receptor and post-receptor signaling pathway AMPK, as indicated by pretreatment with an IMD receptor antagonist or AMPK inhibitor blocking the inhibition of VSMC calcification and upregulation of Sirt3 by IMD1-53. AMPK inhibitor treatment reversed the effects of IMD1-53 on restoring the MMP level and inhibiting mitochondrial oxidative stress in calcified VSMCs. In conclusion, IMD attenuates VC by improving mitochondrial function and inhibiting mitochondrial oxidative stress through upregulating Sirt3.